The effect of various priming techniques on drought stress tolerance and recovery kinetics of Vigna unguiculata L Walp - Aswathi Raj K P (My University, 2025)
his research work was conducted to investigate the impact of different seed priming treatments on the drought stress tolerance potential and recovery kinetics of cowpea. The seeds of four cowpea varieties were obtained from the Regional Agricultural Research Station (RARS) in Pattambi, Kerala, India, and the Kerala Agricultural University (KAU) in Thrissur. Healthy and randomly selected cowpea seeds were surface sterilized and germinated in the culture bottles that contained distilled water (control) and varying concentrations of PEG 6000 (0%, 5%, 10%, 15%, 20%, and 25%), and maintained in a plant growth chamber under controlled conditions. Following the screening procedure, out of the four cowpea varieties, Anaswara was chosen as the sensitive variety and PGCP 6 as the tolerant variety. Priming treatments were conducted in these two varieties with contrasting stress tolerance potential. In order to optimize seedling performance, the concentrations/dosages and duration of priming treatments, such as BABA priming, hydropriming, PEG priming, and UV-B priming, were standardized for the two varieties. According to the preliminary findings, BABA, PEG, and UV-B priming were found to be more efficient against PEG stress in cowpea. Therefore, detailed analysis was performed in the BABA, PEG, and UV-B primed cowpea to evaluate the role of priming on drought stress tolerance. Control plants were kept under well- watered conditions, whereas drought stress was imposed by ceasing irrigation until the leaf relative water content (RWC) decreased to 50%. Subsequent to the stress, the plants were rehydrated for four days to recuperate from drought stress. Osmolytes and osmolality increased during drought stress and reduced during recovery from stress. The content of total soluble sugars, total free amino acids, proline, and total soluble proteins in plants that emerged from primed seeds was significantly higher than in the plants that developed from non-primed seeds. The increased accumulation of osmoprotectants safeguards biomembranes, organelles, and cytosolic enzymes. The drought induced stress effects were assessed by evaluating the accumulation of reactive oxygen species including hydrogen peroxide (H2O2), superoxide (O2•-), and the membrane stability index (MSI), electrolyte leakage, and the degree of lipid peroxidation. During drought stress, cowpea exhibited elevated levels of reactive oxygen species (ROS), leading to membrane damage and lipid peroxidation. The accumulation of ROS was most pronounced in the non-primed sensitive cowpea, causing significant organelle damage. Consequently, there was a reduction in chlorophyll content, reduced absorption,trapping, and electron transport flux per cross section, as well as a lowered performance index, decreased PSI and PSII activity, and a reduced net photosynthetic rate. Seed priming markedly improved the stress tolerance mechanism in cowpea by elevating antioxidant activities. A notable augmentation in enzymatic antioxidants, including SOD, CAT, APX, and GPOX, was reported in drought exposed primed cowpea and it served a vital function in cellular protection and the mitigation of oxidative damage. Upon rewatering, the activities of SOD, CAT, GPOX, and APX were downregulated in cowpea, as their function became negligible due to the rapid recovery of primed cowpea plants from stress. Together with these, non-enzymatic antioxidants were also increased, which offered additional protection. Root length exhibited a slight increase during drought stress, facilitating the extraction of additional water from deeper soil layers; concurrently, lateral root growth, as well as the number and size of root nodules reduced during drought stress. In addition, seed priming with UV-B and BABA enhanced both the number and size of nodules, maybe attributable to the influence of UV-B and BABA on the expression of nod genes or genes involved in flavonoid production. Drought stress significantly reduced the nitrogen (N), molybdenum (Mo) and iron (Fe) content in the root nodules of cowpea varieties studied and the reduction was less in primed plants. RT-qPCR analysis was performed to evaluate the expression of dehydrin genes (DHN) in cowpea under well-watered, drought-stressed, and recovery conditions. The gene expression study revealed that not all dehydrin genes in cowpea are drought-inducible. In the tolerant variety (PGCP 6), only three DHN genes (Vu400, Vu500, and Vu600) were activated during drought stress. The study demonstrates that seed priming with BABA, PEG, and UV-B enhances drought stress tolerance in tolerant cowpea variety and impart drought tolerance in sensitive variety and the extent of tolerance generated by priming was more pronounced in the tolerant variety. Among the priming treatments, BABA priming was proved to be more efficient in mitigating drought stress in the cowpea varieties Anaswara and PGCP 6. BABA priming involves trans-priming, in which the priming stimuli and the prior stress differ in characteristics, perhaps promoting cross-tolerance to stress responses in cowpea. Rewatering alleviated the intensity of drought stress in primed cowpea plants more effectively, promoting a rapid recovery during the recuperation phase. As a result, the BABA primed Anaswara and PGCP 6 exhibited fastest recovery compared to plants subjected to other priming treatments.
Keywords: Antioxidation; Drought; Photosynthesis; Recovery; Seed priming